1988
DOI: 10.1136/adc.63.7_spec_no.719
|View full text |Cite
|
Sign up to set email alerts
|

Dilemmas associated with antenatally detected urinary tract abnormalities.

Abstract: SUMMARY Over a five year period 55 fetuses had abnormalities of the urinary tract detected by antenatal ultrasound scan. The incidence was 1:935 total births during a one year prospective study. Intrauterine intervention was undertaken in five for suspected obstructive uropathy, which was confirmed in only two. Of 51 live born infants, five died (two with renal failure), and only 18 (35%) had a clinically detectable abnormality at birth. Twenty seven patients underwent postnatal operations, the remainder being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 5 publications
3
14
0
Order By: Relevance
“…Diagnostic accuracy in this study is com parable to others reported in the literature with rates varying between 65 and 100% depending on the pathological diagnosis [4,6,9,11,[16][17][18][19][20][21][22], Rizzo [22] showed a diag nosing accuracy of 88, 100 and 66%, with bilateral renal agenesis, polycystic kidneys and unilateral obstructive uropathies, re spectively.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Diagnostic accuracy in this study is com parable to others reported in the literature with rates varying between 65 and 100% depending on the pathological diagnosis [4,6,9,11,[16][17][18][19][20][21][22], Rizzo [22] showed a diag nosing accuracy of 88, 100 and 66%, with bilateral renal agenesis, polycystic kidneys and unilateral obstructive uropathies, re spectively.…”
Section: Discussionsupporting
confidence: 65%
“…This is the exact group that needs to be followed prospectively to see whether there is any ongoing or developing renal abnormalities in the pediatric age group. This lack of appre ciation of the importance of follow-up for this cases has been expressed by other au thors [16] and the need for greater inter change of information between the attending physicians and family practice, obstetrics, ultrasound (radiology), pediatrics and clini cal genetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of the fetal urinary system during antenatal ultrasonography can help diagnose many renal abnormalities, particularly the obstructive type. 5 This should give the physician enough time to educate and prepare the parents and to organize referral of the baby to the appropriate center after birth. Similarly, the importance of diagnosing urinary tract infection in children, particularly the younger ones, cannot be over emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Initially such abnormalities were mainly detected on scans performed late in pregnancy for obstetric reasons. Since the natural history of many of these urinary tract abnormalities was unde®ned, their detection posed many problems in terms of antenatal counselling and postnatal management [20,21].…”
Section: Introductionmentioning
confidence: 99%